VISUALISASI DOA JALAN SALIB MENGADOPSI GAYA WAYANG BEBER DENGAN TEKNIK SENI GRAFIS CUKIL KAYU - Mahendrapati, Alexander Nawangseto (Institut Seni Indoensia Surakarta, 2019)
Research covered titled visualize prayer road crosses by adopting the Wayang Beber style used a woodcut technique of the printmaking is the artistic research (the creation of art) that is carried out based on the art of printing graphic especially a woodcut which is initially be used as a tool to increase religious manuscripts , book illustrations , and then used as propaganda media can be printed because she is the presence of many unique visual and character .Pengkarya use uniqueness in the graphic arts this as an element that reinforce the value estetik and artistic work in visual. This research which was conducted with us is to conduct a study on the degree to which the prayers of devotion road crosses was influential on the strengthening of the value of the true faith admit this catholics in general. The study on Wayang Beber show some years previously had broken also needs to be undertaken of the aspect of visual and if they used these tools as a means of second to disseminate the rudimentary and elemental teachings religious and the good aspects it has done. Through a process go brainstorm and the review of visual artworks in with the theme of or illustration the story of poor reduced to such misery in its course the cross of Jesus Christ was one of those which is borne by their stations of a place of rest the way of a cross in religious place then enacted into a the theme of the creation of the aertwork. The hope is by the creation of the work of the printmaking is due to the activities to give alternarif new in the perspective of all the participants to pray visualization road crosses as well as as a medium for the congregation of the Catholics to are more likely to set on other concerns the road crosses and make him of the love of the faithful for accordance with what god has cope with life.